2012
DOI: 10.1155/2012/704872
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of Osteosarcoma Outcomes in the Modern Medical Era

Abstract: Four decades ago, specialized chemotherapy regimens turned osteosarcoma, once considered a uniformly fatal disease, into a disease in which a majority of patients survive. Though significant survival gains were made from the 1960s to the 1980s, further outcome improvements appear to have plateaued. This study aims to comprehensively review all significant, published data regarding osteosarcoma and outcome in the modern medical era in order to gauge treatment progress. Our results indicate that published surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
322
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 353 publications
(330 citation statements)
references
References 4 publications
3
322
1
4
Order By: Relevance
“…Despite advances in our knowledge of osteosarcoma biology, development, metastasis, and its associated pain, the current treatment options have not changed over the last four decades and continue to rely on tumor resection and nonspeciic combination chemotherapy, which results in a dismal 5-year survival rate of 0-29% for patients with clinically detectable metastases [38,108]. Additionally, severe lack of knowledge regarding osteosarcoma metastasis hinders advancement of clinical treatment in pediatric patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite advances in our knowledge of osteosarcoma biology, development, metastasis, and its associated pain, the current treatment options have not changed over the last four decades and continue to rely on tumor resection and nonspeciic combination chemotherapy, which results in a dismal 5-year survival rate of 0-29% for patients with clinically detectable metastases [38,108]. Additionally, severe lack of knowledge regarding osteosarcoma metastasis hinders advancement of clinical treatment in pediatric patients.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of clinical outcomes of patients without overt metastasis at diagnosis prior to the advent of chemotherapy demonstrated >90% of patients developed lung metastasis 6-36 months after surgical resection, indicating the majority of seemingly nonmetastatic patients actually have micrometastatic disease at diagnosis [30]. While it is largely believed that the implementation of chemotherapy eradicates these developing micrometastases in many cases, these data highlight the fact that metastasis is the most important factor associated with poor outcome in osteosarcoma [38]. Recent work from Moriarity and colleagues identiied many genes that promote osteosarcoma development and metastasis through a forward genetic screen in mice using the SB transposon-based mutagenesis system.…”
Section: Metastasismentioning
confidence: 94%
“…This treatment regimen revealed an increase in the survival rate of patients with localized disease from approximately 20% before the use of chemotherapy, to currently between 60-70% 3,4 . However, in the last two decades, the overall survival of OS patients with local disease has plateaued 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…This treatment regimen revealed an increase in the survival rate of patients with localized disease from approximately 20% before the use of chemotherapy, to currently between 60-70% 3,4 . However, in the last two decades, the overall survival of OS patients with local disease has plateaued 4,5 . Moreover, 30-40% of these patients relapse within 3 years after diagnosis and patients with metastatic disease continue to have a poor survival of 20-30% 4,6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…As a result, patient survival of many types of sarcomas has not been significantly improved over the last few decades. 2 Present-day preclinical sarcoma research, like many other cancer research areas, is largely relying on commercially available 'standard' cell lines, many of which who were developed in the 1950s and 1960s with largely unknown patients history. Recent genetic analyses have shown that with continued passaging of these cells, new genetic changes are introduced as a consequence of the inherent genetic or phenotypic instability of these cell lines.…”
mentioning
confidence: 99%